2018
DOI: 10.15562/phpma.v6i2.14
|View full text |Cite
|
Sign up to set email alerts
|

The association between hypertension self-management and stroke event in male patients at the Badung District Hospital, Bali

Abstract: Background and purpose: Hypertension is a major risk factor for stroke. Despite efforts to control hypertension with pharmacological and non-pharmacological therapies, the prevalence of and death from stroke is reported to be increasing. This study aims to determine the association of hypertension self-management with the incidence of stroke in patients with hypertension.Methods: A case-control study was conducted involving 44 patients suffering from hypertension and who had suffered a stroke as a case, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 13 publications
0
5
0
2
Order By: Relevance
“…In the quantitative and mixed-method studies, body weight management (29 studies 20 , 24 , 25 , 29 , 30 , 33 , 36 , 39–50 , 52 , 53 , 56–62 , 64 ) and physical exercise (22 studies 21 , 22 , 24 , 30–33 , 35 , 38 , 40–43 , 45 , 47 , 52 , 53 , 56 , 57 , 60 , 61 , 75 ) were the most reported, whereas in the qualitative studies, medication adherence and diet intake was the most reported self-care practice. In addition, a few studies described alternative self-care management methods such as stress-relieving methods (6 studies 35 , 40 , 60 , 66 , 68 , 75 ), sleep and rest (2 studies 68 , 74 ), and spiritual fulfilment was described in one study.…”
Section: Self-care and Lifestyle Managementmentioning
confidence: 99%
See 4 more Smart Citations
“…In the quantitative and mixed-method studies, body weight management (29 studies 20 , 24 , 25 , 29 , 30 , 33 , 36 , 39–50 , 52 , 53 , 56–62 , 64 ) and physical exercise (22 studies 21 , 22 , 24 , 30–33 , 35 , 38 , 40–43 , 45 , 47 , 52 , 53 , 56 , 57 , 60 , 61 , 75 ) were the most reported, whereas in the qualitative studies, medication adherence and diet intake was the most reported self-care practice. In addition, a few studies described alternative self-care management methods such as stress-relieving methods (6 studies 35 , 40 , 60 , 66 , 68 , 75 ), sleep and rest (2 studies 68 , 74 ), and spiritual fulfilment was described in one study.…”
Section: Self-care and Lifestyle Managementmentioning
confidence: 99%
“…In the quantitative and mixed-method studies, studies indicated that traditional self-care management, such as body weight management, physical exercise, dietary intake, and medication adherence were poorly practiced. Respectively, studies showed unaddressed risk factors for heart disease and stroke with a 50% incidence or more being reported for overweight/obese (8 studies 20 , 30 , 33 , 50 , 52 , 56 , 57 , 61 ), low level physical exercise (8 studies 21 , 24 , 31 , 32 , 45 , 56 , 57 , 61 ), poor/low-quality dietary intake (9 studies 21 , 23 , 30 , 34 , 40 , 56 , 57 , 60 , 75 ), and poor adherence to medication (4 studies 27 , 32 , 52 , 56 ).…”
Section: Self-care and Lifestyle Managementmentioning
confidence: 99%
See 3 more Smart Citations